2012
DOI: 10.12968/bjon.2012.21.sup1.s10
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective comparative audit of two peripheral IV securement dressings

Abstract: Reliable securement of peripheral venous cannulae (PVC) is an important factor in their maintenance. This audit in a district general hospital compares the occurrence of PVC restarts between a 3-month period in 2010 and the same 3 months in 2011. The only difference in the PVC care bundle between these dates was the implementation of an advanced securement dressing for cannulae in 2011. Results show a significant increase in cannulae attaining the maximum local protocol duration of 72 hours during 2011. Also, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 13 publications
2
15
0
1
Order By: Relevance
“…Studies showed that clinical skill and competency in PVC could reduce the rate of complications (28). The study of Jackson showed that catheters that require removal before 72 hours have complications such as leakage, infiltration and extravasation (17). A study by Abolfotouh et al (2014) reported that from the first 24 to 30 hours complications included extravasation and leakage and on the third day after insertion, all complications were involved (P = 0.0001) (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed that clinical skill and competency in PVC could reduce the rate of complications (28). The study of Jackson showed that catheters that require removal before 72 hours have complications such as leakage, infiltration and extravasation (17). A study by Abolfotouh et al (2014) reported that from the first 24 to 30 hours complications included extravasation and leakage and on the third day after insertion, all complications were involved (P = 0.0001) (29).…”
Section: Discussionmentioning
confidence: 99%
“…Information related to intravenous therapy, including the type of drugs (antibiotics, serum therapy, anticoagulants, etc. ), number of venous catheters (16)(17)(18)(19), the catheter place (back of the hand, forearm, antecubital, on feet and knees), the venous catheter placement (emergency and non-emergency), 3. A checklist of catheterization complications (bleeding, leakage, ecchymosis, obstruction and extravasation) and signs and symptoms of phlebitis based on visual infusion phlebitis assessment scale (VIPAS), with four grades.…”
Section: Methodsmentioning
confidence: 99%
“…After duplicates were removed and titles and abstracts screened, 132 full‐text articles were assessed for study inclusion. After the review of full‐text articles a further 29 articles were excluded as they: included different types of VADs (Renard et al., 2010; Thamby, 2007; Yilmaz et al., 2007); were point‐prevalence audits (Brady et al., 2016; Chiu et al., 2015; do Rego Furtado, 2011; Malach et al., 2006; Powell et al., 2008); did not provide per PVC data (Jackson, 2012; Karadeniz et al., 2003; Norton et al., 2013; Roszell & Jones, 2010); had different outcome definitions (Aulagnier et al., 2014; Coomarasamy et al., 2014; Dunda et al., 2015; Gregg et al., 2010; Holder et al., 2017; Kagel & Rayan, 2004; Mahmoud et al., 2017; Mee‐Marquet et al., 2007; Oto et al., 2011; Prunet et al., 2008; Smith, 2006); reported vascular access procedures (Benham et al., 2007; Chukhraev et al., 2000; Ortiz et al., 2014); were secondary analyses or commentaries on data already included (Danski et al., 2015; Lanbeck et al., 2003; Myrianthefs et al., 2005). Additional information was provided from authors for nine studies (Bugden et al., 2016; Forni et al., 2012; Keogh et al., 2016; Marsh, et al., 2018; Rickard et al., 2010, 2012; Van Donk, 2009; Webster et al., 2007, 2008).…”
Section: The Reviewmentioning
confidence: 99%
“…Evidence supports the use of two options for catheter stabilization of PIVCs ( Fig. 9.3), one for the hub and one as a dressing (Bausone-Gazda et al 2010;Gorski et al 2016;Jackson 2012).…”
Section: Transparent Dressingsmentioning
confidence: 97%